Implementasi Sistem Informasi Akuntansi Berbasis Waterfall dalam Meningkatkan Efisiensi, Akurasi, dan Efektivitas Pengelolaan Keuangan UMKM (Studi Kasus pada Toko Moyasi Motor di Desa Argosuko) - Minan, Ahmad Zida Husni; Amin, Moh.; Junaidi, Junaidi (Universitas Islam Malang, 2026)
The advancement of information technology encourages Micro, Small, and Medium Enterprises (MSMEs) to adopt digital-based accounting systems to improve financial management. However, many MSMEs still rely on manual recording, resulting in inefficiency, errors, and delays in financial reporting. This study aims to analyze the implementation of an Accounting Information System (AIS) using the Waterfall method and its impact on efficiency, accuracy, and effectiveness of financial management. This research employs a qualitative case study approach at Toko Moyasi Motor, located in Argosuko Village, Poncokusumo District, Malang Regency. Data were collected through interviews, observation, and documentation, and analyzed using the interactive model of Miles and Huberman. The results show that the Waterfall-based AIS improves operational efficiency, enhances data accuracy by reducing human error, and supports more effective business decision-making. The findings also support the Diffusion of Innovations theory.Keywords: Accounting information system, waterfall method, efficiency, accuracy, effectiveness